Cognition And Institutional Setting Undergraduates' understandings of the derivative - Bingolbali, Erhan; Monaghan, John (Springer, 2008)
This chapter examines Mechanical Engineering and Mathematics undergraduates' understanding of the derivative and addresses institutional issues in the social formation of knowledge. It summarises results from a study and examines student and lecturer data. Significant differences over the course of the first year are noted. It is claimed that these differences arise from their participation in different departments (institutions). The closing section examines students' developing conceptions of the derivative in institutional settings by addressing the question: what brought about these changes in students' conceptual development?
Keywords: derivative; cognition; institutional setting; departmental affiliation; engineering and mathematics students